Slogans: uma análise fraseológica e linguístico-cultural - Santos, Leonardo Fernandes dos (2021)
This work aims to provide a study of slogans in its phraseological aspect as well as cultural linguistic one. For this, we selected Brazil publicity slogans dated from 1964 up to 2019, dividing them into decades so as to include their historical contexts in the analysis. We were supported by slogans concepts mainly the ones from Iasbeck (2002), Reboul (1975) and Jaki (2014), as well as by phraseological ones, such as Corpas Pastor (1996), Zuluaga (1975), Ruiz Gurillo (1997), Monteiro-Plantin (2014) and Pamies Bertrán (2002). We brought theoretical basis from slogans, Phraseology and, also, the relation between both, which, eventually, impact on culture. The question which guided this study was to search for the understanding of the slogans-phraseologisms relation. A description of phraseologisms’ characteristics featured on slogans was made to justify that slogan transformation into a phraseological unit. Besides that, we also did the opposite way, to understand through examples possible reasons of phraseological units’ use in slogans, being these PUs (Phraseological Units) unautomated or not. We also raised some implications which may occur from this relation, in other words, the power of language on influencing culture through slogans which become popular and idiomatic expressions, as approached by Bourdieu (2008) This study used a qualitative approach, it’s deductive and follows the exploratory model. The occcurence of the slogans transformation into PUs’ phenomenon will be described. 43 slogans(political, institutional and marketing ones) were selected and analysed under the Phraseological perspective coming to a conclusion that slogans are likely to become PUs. The investigation of the relation between slogans and phraseologisms, as well as the linguistic-cultural consequences originated from it were the guide to this study, which is believed to have contributed for a slogan categorization within the phraseological field.